2020
DOI: 10.2174/1874467213666191227104646
|View full text |Cite
|
Sign up to set email alerts
|

Radio-Susceptibility of Nasopharyngeal Carcinoma: Focus on Epstein- Barr Virus, MicroRNAs, Long Non-Coding RNAs and Circular RNAs

Abstract: Nasopharyngeal carcinoma (NPC) is a type of head and neck cancer. As a neoplastic disorder, NPC is a highly malignant squamous cell carcinoma that is derived from the nasopharyngeal epithelium. NPC is radiosensitive; radiotherapy or radiotherapy combining with chemotherapy are the main treatment strategies. However, both modalities are usually accompanied by complications and acquired resistance to radiotherapy is a significant impediment to effective NPC therapy. Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 137 publications
1
13
0
Order By: Relevance
“…NPC patients often complain sixth nerve palsy and Horner's syndrome [2]. At present, the applied treatment predominantly consists of radiotherapy, and integrated radiotherapy and chemotherapy [3]. Unfortunately, radiotherapy and chemotherapy are unexpectedly accompanied by complications, and acquired resistance to radiotherapy hampers the outcomes of NPC [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NPC patients often complain sixth nerve palsy and Horner's syndrome [2]. At present, the applied treatment predominantly consists of radiotherapy, and integrated radiotherapy and chemotherapy [3]. Unfortunately, radiotherapy and chemotherapy are unexpectedly accompanied by complications, and acquired resistance to radiotherapy hampers the outcomes of NPC [3].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the applied treatment predominantly consists of radiotherapy, and integrated radiotherapy and chemotherapy [3]. Unfortunately, radiotherapy and chemotherapy are unexpectedly accompanied by complications, and acquired resistance to radiotherapy hampers the outcomes of NPC [3]. Given that the task to delve out potential targeted therapy ranks a priority.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Epstein-Barr virus (EBV)-encoded products, microRNAs (miRNAs), long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) have been identified in existing research as having common signalling pathways that perform many functions in NPC. 10 Non-coding RNAs, including miRNAs and lncRNAs, have powerful biological functions in cancer. The involvement of ncRNAs in the regulation of tumour proliferation, migration and invasion has been demonstrated in many studies [11][12][13] and is related to chemotherapy resistance and radiation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…circRNAs are a class of noncoding RNA molecules that do not have a 5 0 end cap and a 3 0 end poly (A) tail and form a circular structure with covalent bonds. 12 circRNAs are stably expressed in eukaryotic cells and their expression level is specific to cells and developmental stages. Studies have shown that circRNAs are related to the occurrence and development of various human diseases such as diabetes, atherosclerosis, neurological degeneration, and tumors.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between circRNA in serum exosomes and prognosis of patients with NPC is less studied. circRNAs are a class of noncoding RNA molecules that do not have a 5′ end cap and a 3′ end poly (A) tail and form a circular structure with covalent bonds 12 . circRNAs are stably expressed in eukaryotic cells and their expression level is specific to cells and developmental stages.…”
Section: Introductionmentioning
confidence: 99%